Pengembangan Modul berbasis Isu-Sosiosaintifik pada Topik Bioteknologi untuk Meningkatkan Kemampuan Pemecahan Masalah dan Berpikir Kreatif Peserta Didik - Majlaini, Hanifah; Edi, Sayhmi; Hasairin, Ashar (Biosfer: Jurnal Pendidikan Biologi, 2025)
In the 21st century, education demands students to master essential skills like problem-solving and creative thinking. However, some studies show that Indonesian students, especially in biotechnology, still struggle with these skills. This highlights the need for effective teaching materials, such as SSI-based modules to help students improve their skills. This study aimed to develop a feasible module-based SSI on biotechnology, improve problem-solving and creative thinking skills, and evaluate students' responses to the module-based SSI on biotechnology. The module was developed using the 4D model (Define, Design, Develop, and Disseminate). The sample for this study was 60 students in 11th Grade Science Class from MAN Pematangsiantar. The research findings were as follows: 1) The module feasibility categorized as “excellent” in both media design  and language, while model content categorized as “good” 2) The result of N-gain for problem-solving was 0.61 (medium) and creative thinking was 0.73 (high). 3) Students' responses to the module categorized as “excellent”. Based on these results, the module based-SSI on biotechnology is considered highly feasible and can be used as a learning material that enhances problem-solving and creative thinking skills.